Urgensi Pengelolaan Kelas Dalam Meningkatkan Motivasi Belajar Siswa - Mustikaati, Wina; Izmala, Athariah; Hayati, Ela; Mulyani, Siti Hanisa; Laura, Putri; Maulida, Syaira (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explore the urgency of classroom management in improving students' learning motivation. The problem behind this research is the finding that students tend to be passive in learning, characterized by the lack of questions asked and the results of learning evaluations that are not optimal. A simple survey also shows that more than 60% of students feel less motivated in learning. This condition is reinforced by indications that the learning process is still dominated by conventional methods that do not actively involve students. The research method used is literature review. Through the analysis of relevant data, this research seeks to find a significant relationship between good classroom management and increased student learning motivation. The results highlight the importance of effective classroom management to overcome the problem of student passivity, increase motivation and optimize learning outcomes. It also examines the factors that influence classroom management as well as effective classroom management strategies.